2017
DOI: 10.1159/000475655
|View full text |Cite
|
Sign up to set email alerts
|

Negative Effect of Ellagic Acid on Cytosolic pH Regulation and Glycolytic Flux in Human Endometrial Cancer Cells

Abstract: Background/Aims: Key properties of tumor cells include enhanced glycolytic flux with excessive consumption of glucose and formation of lactate. As glycolysis is highly sensitive to cytosolic pH, maintenance of glycolysis requires export of H+ ions, which is in part accomplished by Na+/H+ exchangers, such as NHE1. The carrier is sensitive to oxidative stress. Growth of tumor cells could be suppressed by the polyphenol Ellagic acid, which is found in various fruits and vegetables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 36 publications
(53 reference statements)
1
19
0
Order By: Relevance
“…Such low pH e inside solid tumors is mainly attributable to the pH i extruders, such as Na + -H + exchanger (NHE) and Na + -HCO 3 -exchanger (NBC) [6,7]. Indeed, NHE activation has been found to enhance tumor cell migration and invasion by creating a distinct cell surface pH gradient and invadopodial-dependent extracellular matrix degradation in human endometrial cancer cells, human breast carcinoma and melanoma cells [8][9][10][11][12]. On the other hand, change of pH i affects many mammalian cellular functions, such as ion channel permeability [13], cell volume [14], proliferation, apoptosis, differentiation and metastasis [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Such low pH e inside solid tumors is mainly attributable to the pH i extruders, such as Na + -H + exchanger (NHE) and Na + -HCO 3 -exchanger (NBC) [6,7]. Indeed, NHE activation has been found to enhance tumor cell migration and invasion by creating a distinct cell surface pH gradient and invadopodial-dependent extracellular matrix degradation in human endometrial cancer cells, human breast carcinoma and melanoma cells [8][9][10][11][12]. On the other hand, change of pH i affects many mammalian cellular functions, such as ion channel permeability [13], cell volume [14], proliferation, apoptosis, differentiation and metastasis [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, increased expression of COX1 and COX2 seemed to be involved in the acidity-enhanced gastric cancer cell invasion, and the anti-invasive role of ellagic acid may be associated with suppression of COX1 and COX2 induction, although inhibition of COX activity was not sufficient for complete prevention of cell invasion. On the other hand, in endometrial cancer cells, high concentration of ellagic acid was shown to reduce the expression of the Na/H+ exchanger NHE1, a regulator of extracellular acidity often overexpressed in cancer cells [18]. To determine if the inhibitory role of ellagic acid on acidity-induced gastric cancer cell invasion is associated with the regulation of NHE1 expression, we detected the effect of ellagic acid on NHE1 expression; however, low concentration of ellagic acid hardly affected NHE1 protein expression in these cells.…”
Section: Ea Decreases Induction Of Cox1 and Cox2 Which Are Involved mentioning
confidence: 99%
“…[10][11][12] Therapeutically, EA has been proclaimed to be effective in the regression of various kinds of tumors, involving but not limited to lung cancer, colorectal carcinoma, esophageal cancer, metastatic melanoma, hepatocellular carcinoma, tongue cancer, breast cancer, bladder cancer, endometrial carcinoma, and prostate cancer. 4,16,[18][19][20][21][22][23][24][25] Whereas the pharmacological effect of EA has been broadly considered and permitted for the management of a vast spectrum of cancer, it still has poor aqueous solubility and poor bioavailability that offer minimal therapeutic benefit and restrict its full clinical use. 26 Oral administration showed a poor absorption, metabolism in gastrointestinal tract, first-pass effect, and rapid elimination, 19,27,28 which are reported as the main causes of its low bioavailability.…”
Section: Introductionmentioning
confidence: 99%